Assessment of the mechanical and microstructural performance of waste kraft fibre reinforced cement composite incorporating sustainable eco-friendly additives - Taiwo, Anuoluwapo Samuel; Ayre, David; Khorami, Morteza; Rahatekar, Sameer S. (MDPI, 2024)
This study investigates the influence of limestone powder and metakaolin as sustainable eco-friendly additives on the properties and behavior of cementitious composite boards, with a focus on mechanical strength, physical properties, and microstructural characteristics. The experimental investigation begins with the characterization of the raw materials, including limestone powder, and metakaolin, to assess their particle sizes, elemental composition, and microstructural features. Cement composite boards were fabricated using an innovatively developed lab-simulated vacuum dewatering process, by varying the proportions of limestone powder and metakaolin as partial replacements for cement, along with waste kraft fibres as reinforcement. Mechanical testing was conducted to evaluate the flexural strength and behaviour of the composite boards according to standardized procedures. A microstructural analysis was performed using scanning electron microscopy (SEM) to examine the effect of additives on the cementitious matrix, fibrematrix interaction, and hydration products. The findings from the experimental study reveal insights into the influence of limestone powder and metakaolin on the mechanical properties and microstructure of waste kraft fibre-reinforced cement composite boards. Our analysis of the results shows that adding 9% limestone powder as partial cement replacement produces a 24% and 50% enhancement in flexural strength at 7 and 28 days of hydration, while that of metakaolin as partial cement replacement was optimum at 6% with an enhancement of 4% and 36%, respectively, at 7 and 28 days of hydration. The implications of these findings for the development of sustainable cementitious composite are discussed, including the potential benefits of using limestone powder and metakaolin as supplementary cementitious materials in waste kraft fibre-reinforced cement composite boards. Finally, recommendations for optimizing additive proportions are also provided to enhance the understanding and application of these materials in the construction and building industries.
Keywords: 4005 Civil Engineering; 40 Engineering; 33 Built Environment and Design; 3302 Building; 11 Sustainable Cities and Communities; 12 Responsible Consumption and Production; 3301 Architecture; waste cardboard paper; fibre cement board; calcium carbonate; kaolinitic clay; mechanical properties; building applications